Spray drying of pectin obtained from Citrus Sinensis waste - Robaina-Mesa, Malvis; Rodriguez Chanfrau, Jorge Enrique [UNESP] (Biointerface Research Applied Chemistry, 2020)
Polysaccharides are high molecular weight polymers that have functional groups, which can be used as sites to derivate or bind specific ligands. Pectin is a polysaccharide that is obtained from plant resources mainly from citrus plants. It is a widely used product in the food and in the pharmaceutical industry for its thickener, stabilizing and gelling properties. The objective of this work was to establish a pectin drying process obtained by acid hydrolysis from citrus waste by spray dry. An acid extraction process with the dry and ground plant material was used. The influence of the inlet and outlet temperatures on the yield and drying speed was evaluated by an experimental design 32 replicated at the central point. With the best variant, five batches were developed at laboratory scale and one batch at bank scale, evaluating the obtained material by infrared spectroscopy and scanning electron microscopy. The results of experimental design showed that the temperature does not influence significantly the yield, but it does affect the speed of the drying. An input-output temperature ratio of 200/80 degrees C was established as the best drying variant. The batches prepared on a laboratory scale showed a yield higher than 85.0% and a drying speed higher than 0.7 L / h. The yield of the batch on a bank scale was 90%. The degree of esterification was 63.5%, indicative of a high degree of methoxylation pectins. The results show that the drying process is adequate to obtain pharmaceutical grade pectin.
Keywords: Pectin; Acid extraction process; Degree of esterification; Spray dry; Infrared Spectroscopy; Electron Microscopy